IMPLEMENTASI PERATURAN BUPATI GIANYAR NOMOR 50 TAHUN 2018 TENTANG GERAKAN MASYARAKAT HIDUP SEHAT DI KABUPATEN GIANYAR - Sri Suliatini, Ni Made; Wirata, Gede; Sriwidnyani, Ida Ayu Putu (Magister Administrasi Publik Program Pascasarjana Universitas Ngurah Rai, 2021)
The Healthy Living Community Movement is a systematic and planned action carried out jointly by all components of the nation with awareness, willingness and ability to behave in a healthy manner to improve the quality of life. The Healthy Living Community Movement in Gianyar Regency is supported by Gianyar Regent Regulation Number 50 of 2018. This study aims to determine and analyze the implementation of Gianyar Regent's Regulation Number 50 of 2018 concerning Healthy Living Community Movement in Gianyar Regency. This research is a qualitative descriptive study based on the theory of Merilee S. Grindle. Collecting data through interviews, documentation and observation with 12 informants. Based on the results of the research, it has described an effort that has been carried out in a coordinated manner, the process has been running in accordance with referring to policy actions. The impact on society individually and in groups is still not optimal. Barriers and problems still exist in implementing The Healthy Living Community Movement policy. The conclusion of this study is that the implementation of the Gianyar Regent's Regulation Number 50 of 2018 has been implemented and is still running until now, but support from cross-sectoral and community is still needed.